EFFECT OF ORGANIC MULCHING TIME ON THE GROWTH OF CASHEWS (Anacardium occidentale) - Yazza Cappy Yoland Harahap; Maria Imelda Humoen; Egidius Naitkakin; Franky Rionaldo Lay (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
Mulching is a soil and water conservation technique widely used in cultivation systems. Mulching functions to suppress groundwater evaporation, inhibit weed growth, and improve soil physical conditions. This study was conducted with the aim of determining the effect of mulching time on the growth of cashew (Anacardium occidentale) seedlings. The study was conducted at the Faculty of Military Logistics Vocational, Indonesian Defense University, Belu, East Nusa Tenggara Province, and was conducted in April–May 2026 using a single-factor Completely Randomized Design (CRD) and using three treatments: P0 (control), P1 (mulching 7 days after planting), and P2 (mulching 14 days after planting). The parameters tested in this study were plant height, stem diameter, number of leaves, root length, wet weight of the stover, and dry weight of the stover. The results showed that mulching did not significantly affect the growth of cashew seedlings. Mulching 7 days after planting gave the highest growth results in the parameters of plant height (18 cm), stem diameter (5.87 mm), number of leaves (6 pieces), root length (8.33 cm), wet weight of the stover (6.53 g), and dry weight of the stover (2.67 g).